Hybrid Arc Could Combine the Benefits of IMRT and VMAT to Deliver a Fast, Conformal, Homogeneous Treatment in Non-Small Cell Lung Cancer without Limitations of Low Dose Bath: A Planning Study - Saglam, Yucel; Bolukbasi, Yasemin; Alpan, Vildan; Topkan, Erkan; Kirsner, Steve; Ballo, Matthew; Chang, Joe Y.; Bingolbali, Ayhan; Selek, Ugur (AKAD DOKTORLAR YAYINEVI, 2017)
Intensity Modulated Radiotherapy (IMRT, step and shoot) is emerging as the standard of care in non-small cell lung cancer (NSCLC) patient treatments. Volumetric Arc Therapy (VMAT) delivered with two arcs offers fast and homogeneous dose delivery with known limitations of increased volumes of low dose. The aim of this study is to define whether Hybrid volumetric arc IMRT (HA-IMRT: IMRT and VMAT combination) offers a superior dose distribution over IMRT without the limitations found in VMAT delivery alone. Ten (previously 4DCT planned) locally advanced NSCLC patients treated by IMRT to 70 Gy in 35 fractions were retrospectively re-planned using the HA-IMRT technique. Respiratory correlated imaging (3 mm slice thickness) were generated utilizing the Philips Large Bore 16 slice CT Scanner (Phillips, Inc.). Treatment planning was performed using The Philips Pinnacle Treatment Planning System v. 9.0 (Philips Medical, Cleveland, OH). The PTV was defined as the Integrated Tumor Volume (ITV=internal GTV contoured on all respiratory data sets plus 8 mm margin for all histologies) with a 4 mm margin added. Lung parenchyme was defined and contoured using the 50% phase. Conventional IMRT plans used 6:8 non coplanar or coplanar fields and VMAT plans were generated using two 180 degrees arcs. HA-IMRT plans were generated using a combination of 60% conventional IMRT with 40% VMAT. The maximum dose (Gy) to the spinal cord, V5, V10, V20 for total lung, V20 and V30 for the ipsilateral lung, V30 for heart, V50 and V70 for esophagus, and the V77 for the Clinical Treat Volume (CTV) were compared for all techniques utilizing the Dose Volume Histograms. In addition, total monitor units (MU), total treatment time (I I) and the conformality index (CI) were compared.. Conventional IMRT delivers less low dose to the lung compared to VMAT alone. (V5 VMAT (V5: 55.0% vs 63.0%, p=0.005; V10: 41.4% vs 43.9%, p=0.018). However, VMAT is superior in total lung V20 (V20:30.6% vs 29.3% p=0.010), ipsilateral lung doses (V20:55.5% vs 52.8% p=0.008; V30: 46.1% vs 42.9% p= 0.012), and in heart sparing. (V30: 21.09% vs 17.78% p=0.015; MHD: 15.92% vs 14.81% p=0.021). It is also superior in conformality (CI 1.51 vs 1.26 p=0.005) and treatment delivery is faster ( 293 min vs 108 min p=0.005) with lower MUs (24805 vs 19141 p=0.005). HA-IMRT was found to be superior to VMAT in terms of total lung low dose volumes (V5:58.1% vs 63.0%, p=0.005; V10:42.2% vs 44.9%, p=0.027), superior to IMRT for ipsilateral lung doses (V20: 53.6% vs 55.5%, p=0.007; V30: 43.4% vs 46.1%, p=0.018), and superior in treatment time (199 min vs 293 min, p=0.005) with lower MU's (22155 vs 24805, p=.005). Overall, HA-IMRT provides a more homogenous dose distribution (CTV: V77: 0.55% vs 2.1% vs 1.7%, p=0.000) compared to IMRT and VMAT alone. All three plans provided comparable esophagus and spinal cord Organ at Risk (OAR) doses. HA-IMRT seems to combine the benefits of both conventional IMRT and VMAT; such as to deliver a faster, more conformal, homogeneous treatment in comparison to ssIMRT, and to deliver lower dose to lung in comparison to VMAT.
Keywords: VMAT; IMRT; Hybrid; Stage III lung cancer; INTENSITY-MODULATED RADIOTHERAPY; RADIATION-THERAPY; CHEMOTHERAPY; CONCURRENT; TOXICITY; OPTIMIZATION; EXPERIENCE; ESOPHAGUS; VOLUME; Oncology